Digital Ethnography of Nongnong Mbaham: Oral Literature Revitalization for Cultural Identity and Contextual Learning Innovation in Papuan Education - Lefaan, Adolina Velomena Samosir; Rambet , Rommy Denny Boy; Darihastining, Susi; Maisaroh, Siti (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study investigates Nongnong Mbaham as a living oral tradition, examines its transformation within digital environments, and explores its potential as a contextual learning innovation in Papuan educational settings.Methodology: A qualitative digital ethnographic approach was employed, involving participant observation, in-depth interviews, performative analysis, and digital-trace analysis across offline and online cultural spaces.Main Findings: This study demonstrates that indigenous oral literature can function as a culturally grounded learning resource that supports identity formation, digital literacy, and contextual pedagogy.Novelty/Originality of this study: This research advances oral-literature studies by integrating digital ethnography with contextual learning innovation, moving beyond documentation toward a sustainable educational revitalization model.